PENDEKATAN MODEL FUNGSI TRANSFER MULTI INPUT UNTUK ANALISIS HUBUNGAN ANTARA LUAS PANEN DAN LUAS TAMBAH TANAM DENGAN PRODUKSI BAWANG MERAH DI JAWA TENGAH - Yunisa Ratna Resti; Abdul Hoyyi; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Onion is one of holticulture commoditie which is consumed by many Indonesians with Central Java as its largest producer. The consumer’s need of onion keeps raising but, unfortunately, its number in the marketplace is limited. The onion supply depend on onion’s production which is affected by some factors, such as the land condition from the beginning when cultivation is started until the harvesting come such as area of harvesting and area of additional cultivation. So that onion’s production modeling which influenced by significant factores is needed to predict the crops volume in the future. Data which is used to production modeling are data of onion’s production in Jawa Tengah, these data is written by Dinas Pertanian Tanaman Pangan dan Hortikultura Jawa Tengah in everymonth. This research use multiple input transfer function model, which is an integration of ARIMA and regression model. This reseach aimed at modelling output series of onion production using two input series, i.e. area of harvesting and area of additional cultivation, from January 2004 to November 2014. The result showed that there is a significant correlation between area of harvesting and onion production, starting from lag t=0 during two periods, as well as area of additional cultivation toward the production from lag t=0. This multiple input transfer function method resulted in AIC valued at 3088.484. Keywords: Multiple Input Transfer Function, Onion